2020
DOI: 10.1155/2020/2452409
|View full text |Cite
|
Sign up to set email alerts
|

Cell-to-Cell Spread of Dengue Viral RNA in Mosquito Cells

Abstract: Dengue virus (DENV) is an important mosquito-borne arbovirus that is particularly prevalent in tropical and subtropical areas of the world. The virus is generally ingested with a blood meal, replicates in host tissues, and disseminates into salivary glands for transmission to the next host. Membrane-bound vacuoles carrying DENV particles have been documented in mosquito cells and play a role in the cell-to-cell transmission of DENV2. C189 is one member of the tetraspanin family and generally increases its expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 44 publications
1
7
0
Order By: Relevance
“…This study further observed increased cell-to-cell transmission of DENV at the site where the donor cell directly interacts with the recipient cell (7). A recent study has shown that tetraspanin C189 containing vacuoles mediate cell-to-cell spread of viral RNA within DENV2infected C6/36 cells (See Table 1) (43). Magnetic immune isolation (MI) and sucrose gradient centrifugation showed that DENV2 RNA is transmitted by C189-VCs from donor to recipient cells.…”
Section: Arthropod Tetraspanins In Virus-host Interactionssupporting
confidence: 62%
See 2 more Smart Citations
“…This study further observed increased cell-to-cell transmission of DENV at the site where the donor cell directly interacts with the recipient cell (7). A recent study has shown that tetraspanin C189 containing vacuoles mediate cell-to-cell spread of viral RNA within DENV2infected C6/36 cells (See Table 1) (43). Magnetic immune isolation (MI) and sucrose gradient centrifugation showed that DENV2 RNA is transmitted by C189-VCs from donor to recipient cells.…”
Section: Arthropod Tetraspanins In Virus-host Interactionssupporting
confidence: 62%
“…Magnetic immune isolation (MI) and sucrose gradient centrifugation showed that DENV2 RNA is transmitted by C189-VCs from donor to recipient cells. Viral RNA was only detected in recipient cells in transwell system, indicating that cell-cell contact is essential for DENV2 intercellular spread (43).…”
Section: Arthropod Tetraspanins In Virus-host Interactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…DENV infection is generally initiated by cell-free viruses in the mosquito midgut, likely followed by the cell-to-cell mode of dissemination to their destination, i.e., salivary glands. In cultures of mosquito cells with DENV2 infection, virions and viral RNA carried by vacuoles (VCs) were demonstrated to transfer from one cell to its neighbors via the cell-to-cell transmission mode [ 70 , 71 ]. During the transmission process of this virus, a novel tetraspanin called C189 is induced and is incorporated as a membrane component of VCs (C189-VCs) formed in response to DENV infection in mosquito cells [ 72 ].…”
Section: Infection Dissemination and Effects Of The Denv In The mentioning
confidence: 99%
“…The VC is presumed to serve as a vehicle which carries the virus from one cell to its neighbors. Moreover, a “viral synapse” (VS) located in the intercellular space is frequently formed [ 71 ], which was also observed at the interface between donor and recipient cells during cell-to-cell transmission of HIV [ 65 ]. The formation of VCs in humans may play a role of helping the virus evade humoral immunity, resulting in rapid transmission and continued infection of the host [ 73 ].…”
Section: Infection Dissemination and Effects Of The Denv In The mentioning
confidence: 99%